Effect of Melt Cooling Condition on As and Pb Elution Properties in Copper Slag - Chika ONISHI; Shuto YOSHIFUKU; Hiromichi TAKEBE (Journal of MMIJ, 2022)
Copper slag (CS) granules received from a Japanese smelter were melted using an alumina crucible under Ar gas flow in an electric furnace. The melt was removed from the furnace and cooled slowly with various holding times in air and then water-quenched. The increase of cooling time in air promoted the partial crystallization of CS samples: the separation of Fe-rich and Si-rich phases, the precipitation of fayalite and magnetite phases and the formation of Al2O3- and SiO2-rich non-crystalline aluminosilicate phase. The CS melt was subdivided into smaller ones through a hand-made yttria-doped stabilized zirconia polycrystal sieve and repelled by a rotational graphite plate. After cooling crystallized CS granules were successfully fabricated. The crystallized CS granules including fayalite and magnetite phases satisfied a lower limit for the elution amounts of As and Pb fixed as ≤150 mg/kg in 1 mol/L HCl aqueous solution as specified in the guideline of JIS 0058-2:2005 as a test method for acid-extractable contents of chemicals.